PTH-204 Using remote monitoring to detect infusion related issues in patients on home parenteral nutrition. (22nd June 2015) - Small, M; Kallis, M; Tsoukalis, A; Cascailh, JC; Gabe, SM
Abstract : Introduction: Infusion history is a vital part of monitoring patients on home parenteral nutrition. This has traditionally relied on informal methods such as patient recall, measurement of stock used and/or ordered. Little is known of infusion rates, hours infusing, or if patients regularly under or over infuse. Liaison with industry revealed technology allowing monitoring of patient's infusion histories. The aim of this study was to use these histories to determine infusion patterns and if any infusion related issues could be identified. Method: 20 patients consented to have their infusion histories monitored. Histories were recorded on the Micrel PN+ pump and exported anonymously using GPRS technology to a secure Micrelcare™ server. Any patient regularly under or over infusing was contacted to see if any infusion related problems could be established and remedied. Results: 1350 infusions were recorded over 12 weeks from 20 patients, mean 5.3 ± 1.7 (2–7) nights per week. Mean infusion time 11.1 ± 1.9 (range 6–15) hours, mean infusion rate 176 ± 73.2 (range 83–330) ml/hour. Parenteral nutrition volume prescribed was 2, 692 litre, actual infused 2, 098 litre (78%). There was good correlation between these values (r = 0.81). The mean volume infused per patient was 77 ± 0.32 (23–141)%. 3 (20%) patients under infused every infusion. Patient 1 has headaches (known venous stenosis) at 250ml/hour so reduces rate to 200ml/hour but will not increase infusion time. Patient 2 was concerned about weight gain so adjusted prescription herself. This has now been changed and patient has an extra night off. Patient 3 felt bloated and described facial swelling so only infuses half of each bag. This trend continues despite clinical evaluation showed no thrombosis or fluid overload. 3 (20%) patients regularly over infused. Patient 4 had considerable overage in her infusion, which has been reduced. Patient 5 had had their prescription reduced from 5 nights per week to 3 but felt anxious about the change so continued to infuse intravenous fluid on her nights off. Patient 6 was concerned about pump under delivery so infused additional fluid to compensate. Review of her infusion history showed that she was receiving the entire prescription and the additional infusions have stopped. Conclusion: Assessing patient's infusion histories revealed a wide variation in infusion rates and hours infusing. Overall compliance with the prescribed parenteral nutrition regimen was good, and where there were discrepancies there was usually a valid explanation. Being able to review an individual's infusion history will undoubtedly assist in the ongoing assessment of patient's requirements and hopefully reduce the number of unnecessary infusions or inappropriate prescription changes. Disclosure of interest: M. Small: None Declared, M. Kallis Paid Instructor for: Micrel Medical Devices, A. Tsoukalis Employee of: Micrel Medical Devices, J. Cascailh Employee of: Micrel Medical Devices, S. Gabe: None Declared.